2018
DOI: 10.12965/jer.1836056.028
|View full text |Cite
|
Sign up to set email alerts
|

Skin temperature changes during muscular static stretching exercise

Abstract: This study aimed to investigate the acute effects of stretching exercise on skin temperature, flexibility, passive muscle stiffness, and pain during hamstring stretching in healthy young subjects. Thirty-one participants (n=31) were randomly divided into 2 groups: an experimental group (EG, n=15), which was submitted to hamstring stretching exercise for 180 sec, and the control group (n=16), which was not exercised. Skin temperature (TsK) was collected in subjects’ posterior thigh using a thermographic camera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
6
0
3
Order By: Relevance
“…Studies have reported that adults with a sedentary lifestyle have less hamstring flexibility (De Oliveira et al, 2018). Cho et al (2017) observed a significant relationship between physical activity level and hamstring flexibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported that adults with a sedentary lifestyle have less hamstring flexibility (De Oliveira et al, 2018). Cho et al (2017) observed a significant relationship between physical activity level and hamstring flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of stretching exercises can be used to increase hamstring flexibility (De Oliveira et al, 2018). In their study comparing the effectiveness of active and passive hamstring stretching exercises, Meroni et al (2010) reported that active stretching is more efficient in terms of time use and requires less compliance in terms of performing the exercises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A broad literature entails a multitude of strategies and stretching protocols to obtain specific advantages in flexibility [9,10,46,47]. Nevertheless, only a few studies have included cryo-exposures protocols to assess possible gains in ROM and proprioception acuity [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Lactate measurement can be performed immediately following or even during exercise because it does not require complex laboratory procedures [22]. Thermal imaging allows for a psychologically comfortable evaluation of post-exercise recovery without substantial financial outlays [23].…”
Section: Plos Onementioning
confidence: 99%